Religious discourse as a political tactic: a comparative analysis of David Cameron's God Strategy. Issue 4 (2nd October 2018) - Williams, Anthony A.J.
ABSTRACT: During his time as Prime Minister David Cameron made in speeches and articles a number of references to his own religious beliefs and their impact on policy, interventions which stood out in a largely secularised political culture. This paper examines Cameron's discourse for strategic intent following the God Strategy framework developed by David Domke and Kevin Coe (2008) in a US context and compares Cameron's use of religious discourse to that utilised by presidents of the United States. We will conclude that Cameron was using religion as a political tactic in a manner analogous to that of US presidents, insofar as he used religious language to appeal to Christian voters, argued that the UK should be considered a Christian country, signalled his own religious commitment, and engaged with policy issues important to Christian voters. We will, however, also note key differences between Cameron's use of the strategy and that of his American counterparts which are the result of differences in context and culture, including his engaging with different policy issues to that of his US counterparts, presenting a more cautious picture of his own faith, and limiting the rhetorical arenas in which his God Strategy is employed.